The efficacy and safety of denosumab, risedronate, alendronate and teriparatide to treat male osteoporosis: a systematic review and bayesian network meta-analysis - Chai, Shu Jun; Yu, Tao; Wang, Guo Rui; Sun, Fu Lu; Xue, Hao; Zhang, Zun; Ran, Bo (Frontiers in Endocrinology, 2025)
BackgroundMale osteoporosis treatment lacks robust comparisons of efficacy and safety among key medications. This network meta-analysis (NMA) aimed to systematically evaluate alendronate (ALE), risedronate (RIS), teriparatide (TER), and denosumab (DEN) in male patients, addressing this critical evidence gap.MethodsFollowing PRISMA 2020 guidelines, we conducted a systematic review and NMA. Databases were searched for randomized controlled trials (RCTs) comparing these drugs in males with osteoporosis (PICOS criteria). Pairwise meta-analysis (Stata 18.0) assessed effect sizes, while NMA (R 4.3.1, gemtc and BUGSnet packages) ranked treatments for BMD changes (lumbar spine, femoral neck, total hip) and safety outcomes (adverse and serious adverse events).ResultsFrom 2729 screened records, 12 studies were included. TER ranked highest for lumbar spine BMD improvement and overall safety (lowest adverse events). ALE showed superior femoral neck and total hip BMD gains but higher adverse event risks vs. TER. DEN improved BMD at all sites but had the poorest safety profile (highest adverse events). RIS was safest (lowest serious adverse events) but least effective for BMD enhancement.ConclusionsTeriparatide is the optimal choice for improving lumbar spine BMD and overall safety, while alendronate shows significant efficacy in enhancing femoral neck and hip BMD, although its safety profile is less favorable. Thus, alendronate may be more suitable for patients needing bone density improvement at these sites. Treatment choices should weigh site-specific needs against risk tolerance.Systematic review registrationhttps://www.crd.york.ac.uk/prospero, identifier CRD42024599021.